Inducing apical barrier in fractured non-vital immature permanent incisors using single calcium hydroxide dressing – A case report - OROOJI, Mahsa; MAKSOUD, Rami (International Arab Journal of Dentistry (IAJD), 2013)
Endodontic treatment of immature traumatic non-vital permanent teeth is delicate since open apices and divergent canal walls render the debridement and obturation difficult. Its success depends on the closure of the root apex and the establishment of an apical barrier. Different materials are used for the apexification procedure. Calcium hydroxide apexification is the most common treatment for necrotic, immature permanent teeth. The aim of this report is to present a case of apexification using a single injected calcium hydroxide dressing for the treatment of a necrotic pulp of permanent incisors with wide open apexes in a young patient. The obtained result indicated that an apical stop is created with single visit apexification. Radiologic examination after 5 months showed that the apices of the maxillary incisors are completed by newly formed tissue. In spite of success in apical barrier formation by single visit calcium hydroxide dressing, long-term follow-up of these teeth is necessary.